2022
DOI: 10.3389/fphys.2022.863855
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response and Pulse Arrival Time During Exercise Testing in Well-Trained Individuals

Abstract: Introduction: There is a lack of data describing the blood pressure response (BPR) in well-trained individuals. In addition, continuous bio-signal measurements are increasingly investigated to overcome the limitations of intermittent cuff-based BP measurements during exercise testing. Thus, the present study aimed to assess the BPR in well-trained individuals during a cycle ergometer test with a particular focus on the systolic BP (SBP) and to investigate pulse arrival time (PAT) as a continuous surrogate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In these participants, additionally, the systolic office-home BP difference was no longer associated with the HbA1c value, P = .793. 137 (18) 139 (17) 133 (18) .002 Diastolic 83 (10) 85 (11) 85 (10) 83 (10) .002…”
Section: Study Imentioning
confidence: 99%
See 1 more Smart Citation
“…In these participants, additionally, the systolic office-home BP difference was no longer associated with the HbA1c value, P = .793. 137 (18) 139 (17) 133 (18) .002 Diastolic 83 (10) 85 (11) 85 (10) 83 (10) .002…”
Section: Study Imentioning
confidence: 99%
“…During weight lifting, systolic BP as high as 480 mmHg has been recorded (5). During aerobic exercise, systolic BP can increase by around 40-60%, from normotensive to between 170 to 220 mmHg (9)(10)(11). In fact, although high systolic BP during and after exercise is associated with incident hypertension and increased cardiovascular risk (12)(13)(14), during maximum aerobic exercise, a low rather than a high peak systolic BP is associated with increased mortality (14).…”
Section: Introduction Hypertensionmentioning
confidence: 99%
“…A prototype cuffless BP sensor (cuffless BP device) was used in this study (7)(8)(9). It consists of a one-channel electrocardiogram (ECG) sensor, a photo-plethysmography (PPG) sensor and an inertial measurement unit (3D accelerometer and 3D gyroscope) integrated in a wearable chest belt.…”
Section: Cuffless Blood Pressure Devicementioning
confidence: 99%
“…In addition, non-invasive cuffless BP methods use different approaches such as pulse wave propagation-based measurements (such as pulse arrival time (PAT)) and photo-plethysmography (PPG) waveform features. Studies, including research performed by our multidisciplinary team, have shown strong correlations between PAT and BP, particularly during various exercise methods (5)(6)(7)(8)(9) but its accuracy across differing populations and hemodynamic conditions are uncertain (6). New advances in non-invasive cuffless BP indicate that complex modeling by machine learning methods of sensor-based measurements are key toward improved results (6).…”
Section: Introductionmentioning
confidence: 99%
“…In both normotensive and hypertensive individuals, physical exercise, either dynamic or isometric, carried out in the clinical setting for cardiovascular (CV) diagnostics, is associated to significant blood pressure (BP) variations, in particular sharp increments in systolic BP (SBP) and variable changes in diastolic BP (DBP), that may either decrease, increase or remain unchanged [ 1 , 2 ]. In physiological conditions, BP changes during exercise are the result of the rise in cardiac output in response to the increased oxygen demand from working muscles via activation of the adrenergic tone [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%